What Have We Learnt About the Sourcing of Personal Protective Equipment During Pandemics? Leadership and Management in Healthcare Supply Chain Management: A Scoping Review - Sharon Williams (Frontiers in Public Health, 2021)
Introduction: During the ongoing COVID-19 pandemic there have been much publicised shortages in Personal Protective Equipment for frontline health care workers, from masks to gowns. Recent previous airborne pandemics provide an opportunity to learn how to effectively lead and manage supply chains during crisis situations. Identifying and plotting this learning against time will reveal what has been learnt, when and, significantly, what can be learnt for the future.Aims: (i) To identify the temporal trajectory of leadership and management learning in health supply chain management through pandemics and (ii) to identify leadership and management lessons to enable the resilient supply of key items such as PPE in future pandemics.Methods: We undertook a scoping review in line with PRISMA (scoping review extension) searching Business Source Premier, Health Business Elite, Medline, ProQuest Business Collection and PubMed. Search terms were focused on recent airborne pandemics (SARS; Ebola; Zika virus; H1N1 swine flu, COVID-19), supply chain management, PPE, leadership, learning, inhibitors and facilitators and resilience e.g., SARS AND supply chain* AND (“personal protective equipment” OR PPE) (leaders* OR manage*) Titles and abstracts were downloaded to Endnote and duplicates removed. Two authors independently screened all of the titles and abstracts. Inclusion criteria focused on leadership and management in health supply chains during pandemics, peer reviewed or grey literature (either from business journals or reports): exclusion criteria included not in English and not focused on a named pandemic. Once interrater reliability was assured, authors completed a title and abstract screening independently. Ten percent of the resultant full text articles were screened by both authors, once agreement was reached the full text articles were screened independently noting reasons for exclusion. A data extraction tool was designed to capture findings from the final articles included in the review.Results/Discussion: We found 92 articles and, after screening, included 30 full text articles. The majority were focused on COVID-19 (N = 27) and most were from the USA (N = 13). We identified four themes related to leadership and management of pandemic PPE supply chains, (i) Leadership and management learning for pandemic PPE supply chain management, (ii) Inhibitors of PPE supply chain resilience during a pandemic, (iii) Facilitators employed to manage the immediate impacts of PPE supply chain demands during a pandemic,and (iv) Facilitators proposed to ensure longer term resilience of PPE supply chains during pandemics Our study suggests there has been limited leadership and management learning for PPE supply chains from previous pandemics, however there has been extensive learning through the COVID-19 pandemic. Lessons included the importance of planning, the significance of collaboration and relationship building. Resilience of PPE supply chains was reported to be dependent on multiple levels from individuals to organisation level and also interdependent on (i) sustainability, (ii) the practise of PPE and (iii) long term environmental impact of PPE suggesting the need, long term, to move to a circular economy approach.